Endophytic fungus Colletotrichum sp. AP12 promotes growth physiology and andrographolide biosynthesis in Andrographis paniculata (Burm. f.) Nees - Xu, Dan; Li, Na; Gu, Yuan-Qin; Huang, Jin; Hu, Bin-Sheng; Zheng, Jian-Yun; Hu, Jing-Wen; Du, Qin (Frontiers in Plant Science, 2023)
Endophytic fungi can promote host plant growth, enhance antioxidant defense enzyme activity, and induce the biosynthesis and accumulation of secondary metabolites. Therefore, using endophytic fungi to improve the quality and yield of medicinal plants or important crops is an effective means of regulation. Colletotrichum sp. AP12 has been reported to produce andrographolide compounds (ADCs). This study aimed to investigate the effects of AP12 and its elicitors on the growth, defense enzyme activity, accumulation, and transcription levels of key genes in Andrographis paniculata (Burm. f.) Nees (A. paniculata). The results showed that the AP12 strain prepared inactivated fermentation solution (IFS), fermentation solution (FS), inactivated mycelium solution (IMS), and mycelium solution (MS) and that all four fungal elicitor components (ECs) could promote A. paniculata growth, enhance antioxidant defense enzymes, and increase ADCs content and yield, especially the IMS group had the highest leaf area, whole plant dry weight, superoxide dismutase (SOD), catalase (CAT) enzyme activities, total lactone contents and yields, which were 2.37-, 1.60-, 2.20-, 3.27-, 1.59- ,2.65- fold of the control, respectively. The 14-deoxyandrographolide (NAD) in the host irrigated with MS was 3.35-fold than of the control. In addition, AP12-infected A. paniculata sterile seedlings could significantly increase ADCs content and expression levels of key enzyme genes, especially, on day 12, the total lactone content of the host reached 88.881±5.793 mg/g DW, while on day 6, CPS gene expression level that reached 10.79-fold of the control, in turn promoting the biosynthesis and accumulation of andrographolide. In conclusion, the endophytic fungus AP12 is beneficial to the growth and secondary metabolism of A. paniculata, which is helpful for cultivation and application of biological bacterial fertilizer in A. paniculata, providing a theoretical and research basis for the use of endophytic fungi as a microbial resource to improve the quality and yield of medicinal plants.